OUTCOMES OF PLAY-BASED HOME SUPPORT FOR CHILDREN WITH AUTISM SPECTRUM DISORDER - (:unkn) unknown (SOC PERSONALITY RES INC, 2014)
Play-based home support is an important early education option that leads to positive changes in the development of children who are either at risk of, or have been diagnosed with, developmental disorders. In this case study I analyzed the second year of an education program, based on play-based home support and family education offered to a 4-year-old boy with autism spectrum disorder. I found that: (a) the child demonstrated progress in skills covered by the individualized education, (b) there was a consequential decrease in intensity of autism symptoms, (c) there was evidence of development of the child's attention during playtime, and (d) the child's communication and speech skills showed improvement. The implications of this case study are further discussed in relation to natural learning settings, family cooperation, and early education for children at risk of developmental disorders.
Keywords: developmental disorders; impulse control; play-based home support; early childhood education; autism spectrum disorder; EARLY-CHILDHOOD PROGRAMS; YOUNG-CHILDREN; EARLY INTERVENTION; MAINTENANCE TASKS; BEHAVIOR; MODEL; EDUCATION; SKILLS